2010
DOI: 10.1128/jvi.02478-09
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon-Induced Gene ISG15 Blocks Retrovirus Release from Cells Late in the Budding Process

Abstract: The release of retroviruses from cells requires ubiquitination of Gag and recruitment of cellular proteins involved in endosome sorting, including the ESCRT-III proteins and the Vps4 ATPase. In response to infection, cells have evolved an interferon-induced mechanism to block virus replication through expression of the interferon-stimulated gene 15 (ISG15), a dimer homologue of ubiquitin, which interferes with ubiquitin pathways in cells. Previously, it has been reported that ISG15 expression inhibited the E3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
141
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 54 publications
7
141
0
Order By: Relevance
“…BST-2 blocks the release of HIV-1 particles from the cell surface (44,64). ISG15 impedes HIV-1 virus production by causing ISGylation of viral Gag protein and cellular factors, such as CHMP5 (chromatin-modifying protein 5) (46,47). APOBEC3G restricts HIV-1 replication by causing hypermutation of viral cDNA during reverse transcription (37,57).…”
Section: Type I Interferon Protects Cells From Virus Infection Througmentioning
confidence: 99%
“…BST-2 blocks the release of HIV-1 particles from the cell surface (44,64). ISG15 impedes HIV-1 virus production by causing ISGylation of viral Gag protein and cellular factors, such as CHMP5 (chromatin-modifying protein 5) (46,47). APOBEC3G restricts HIV-1 replication by causing hypermutation of viral cDNA during reverse transcription (37,57).…”
Section: Type I Interferon Protects Cells From Virus Infection Througmentioning
confidence: 99%
“…These interactions allow LIP5 to coordinate ESCRT-III and VPS4 activities both during normal cellular homeostasis and also apparently in response to interferon signaling during innate immune responses. In the latter case, Leis and co-workers (63,64) have reported that covalent modification of CHMP5 and other ESCRT-III proteins with the ubiquitin-like protein ISG15 blocks the LIP5-CHMP5 and LIP5-VPS4 interactions and thereby inhibits enveloped viruses from using the ESCRT pathway to bud from cells. To define better how LIP5 can mediate its different regulatory functions, we have characterized how LIP5 interacts with CHMP5 and other ESCRT-III proteins and determined the interdependence of different LIP5-ligand interactions both in vitro and in cells.…”
mentioning
confidence: 99%
“…Several reports show that ISG15 expression inhibits the E3 subunit of the ligase involved in Gag or Tsg101 ubiquitination, suggesting a possible mechanism for the observed inhibition (14,19,20,44). Disruption of the late release process is a more general antiviral mechanism in which the VPS4 ATPase is removed from the budding complex (25). When ISG15 and its ligase are expressed in cells, CHMP5 becomes ISGylated and accumulates in the membrane fraction (25).…”
mentioning
confidence: 99%
“…A cellular innate immunity mechanism which targets retrovirus budding both early and late in the release process induces the expression of interferon-stimulated gene 15 (ISG15) and its specific ISG15 E1, E2, and E3 ligase complex (3,4,25,27,33,43,45). ISG15 is a dimer homologue of ubiquitin.…”
mentioning
confidence: 99%